PERFORMANCE EVALUATION OF MUTUAL FUND IN INDIA FOR THE PAST 6 YEARS (2004-09) - KAPUR, PAWAN (2009)
Numerous studies have been conducted in the past involving performance evaluation of mutual fund. All these past researches have examined whether mutual fund can beat the market or not and had concluded that mutual fund generally do not outperform the market. This in turn had concluded that markets are efficient and there is no scope for abnormal profits. This research is carried out with the same intentions to investigate whether Mutual fund can beat the market or not. Therefore performance of 21 growth funds are analyzed for the past 6 years from April 2004 to March 2009,which is then compared to BSE-500.Performance of these sample funds are evaluated using different models such as Sharpe ratio, Jensen alpha, Treynor ratio, Information ratio and M-square. The analysis showed that 20 out of 21 funds had been able to outperform the market (BSE-500).This further had concluded that Indian markets are not that efficient.